Grinding comparative between ductile iron and austempered ductile iron under CBN wheel combined to abrasive grains with high and low friability - Daniel, Douglas Maiochi [UNESP]; Avila, Benicio Nacif [UNESP]; Garcia, Mateus Vinicius [UNESP]; Lopes, Jose Claudio [UNESP]; Ribeiro, Fernando Sabino Fonteque; Mello, Hamilton Jose de [UNESP]; Angelo Sanchez, Luiz Eduardo de [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2020)
The grinding process is a finishing operation that guarantees the surface of the workpieces with geometric and dimensional precision. This machining requires significant efforts to remove material, which can cause excessive wheel wear and even distortions on the workpiece surface. Also, the productivity and efficiency of this process are directly affected by the properties of the workpiece, wheel friability, and feed rate. In this context, it is essential to find the best machining conditions. Thus, this article makes a comparative analysis between the cylindrical grinding of SAE D-7003 ductile iron (DI) and SAE D-7003 austempered ductile iron (ADI), with two wheels of cubic boron nitride (CBN), one with low and the other with high friability, using feed rate of 0.50, 1.00, and 1.50 mm/min. The lubri-refrigeration of the process was done by the conventional method. The output parameters evaluated were surface roughness (Ra), roundness error, diametral wheel wear, tangential cutting force, microhardness, and micrograph. The tool with less friable grains reduces the surface roughness by 18%, 21%, and 29% compared with the tool with more friable grains for grinding of the DI with the feed rate of 0.50, 1.00, and 1.50 mm/min, respectively. In the ADI, the surface roughness is reduced by 27%, 26%, and 29% with a feed rate of 0.50, 1.00, and 1.50 mm/min, respectively. The results show that the low friability tool performs better in most parameters.
Keywords: Cylindrical grinding; SAE D-7003 ductile iron; Austempered ductile iron; Friability; CBN wheel